TEVAR Rescue of an Embolized Edwards SAPIEN XT Valve Following TAVR. (October 2015) - Larion, Sebastian; Moore, Jason R.; Ammar, Chad; Panneton, Jean M.
Purpose: To report a successful method of managing an embolized Edwards SAPIEN XT aortic valve prosthesis using a thoracic endovascular aortic repair rescue.Case Report: An 84-year-old man underwent transcatheter aortic valve replacement using a 26-mm Edwards SAPIEN XT valve, which immediately embolized into the ascending aorta. Because of the severe tapering of the patient's transverse aortic arch, the embolized valve was unable to be maneuvered further down the aorta. Therefore, a Cook 36×80-mm Zenith Dissection Endovascular System (ZDES) bare metal stent was used on a compassionate basis to append the embolized valve between the patient's coronary artery ostia and the innominate artery takeoff within the ascending aorta, with no neurological or cardiovascular complications at 12-month follow-up.Conclusion: A Cook ZDES bare metal stent may be successfully used to append an embolized Edwards SAPIEN XT valve within the ascending aorta.